Neurons from human mesenchymal stem cells display both spontaneous and stimuli responsive activity. - Nihal Karakaş (PLoS ONE, 2020)
Mesenchymal stem cells have the ability to transdifferentiate into neurons and therefore one of the potential adult stem cell source for neuronal tissue regeneration applications and understanding neurodevelopmental processes. In many studies on human mesenchymal stem cell (hMSC) derived neurons, success in neuronal differentiation was limited to neuronal protein expressions which is not statisfactory in terms of neuronal activity. Established neuronal networks seen in culture have to be investigated in terms of synaptic signal transmission ability to develop a culture model for human neurons and further studying the mechanism of neuronal differentiation and neurological pathologies. Accordingly, in this study, we analysed the functionality of bone marrow hMSCs differentiated into neurons by a single step cytokine-based induction protocol. Neurons from both primary hMSCs and hMSC cell line displayed spontaneous activity (≥75%) as demonstrated by Ca++ imaging. Furthermore, when electrically stimulated, hMSC derived neurons (hMd-Neurons) matched the response of a typical neuron in the process of maturation. Our results reveal that a combination of neuronal inducers enhance differentiation capacity of bone marrow hMSCs into high yielding functional neurons with spontaneous activity and mature into electrophysiologically active state. Conceptually, we suggest these functional hMd-Neurons to be used as a tool for disease modelling of neuropathologies and neuronal differentiation studies.